Association between ezetimibe usage and hepatitis C RNA levels in uninfected kidney transplant recipients who received hepatitis C infected kidneys. Issue 12 (1st October 2021) - Azhar, Ambreen; Binari, Laura A.; Joglekar, Kiran; Tsujita, Makoto; Talwar, Manish; Balaraman, Vasanthi; Bhalla, Anshul; Eason, James D.; Hall, Isaac E.; Rofaiel, George; Forbes, Rachel C.; Shaffer, David; et al.
Abstract: Kidney transplantation (KT) from hepatitis C virus infected (HCV+) donors to HCV negative recipients achieve excellent graft function but have relatively higher rates of post‐KT co‐infections presumably due to prolonged HCV viremia in transmission‐and‐treat approach. Ezetimibe acts as an antagonist of Niemann‐Pick C1‐Like 1 receptor required for HCV entry and theoretically can reduce HCV viremia. However, no data is available to examine the role of ezetimibe as a bridge therapy between KT surgery and direct acting antiviral (DAA) initiation. A retrospective cohort study including 70 HCV+ to HCV negative KT recipients from Methodist University Hospital and Vanderbilt University Medical Center was performed to determine the association between ezetimibe usage and HCV viremia. Twenty patients received ezetimibe daily while 50 patients did not. Primary outcome of study was mean HCV RNA level at 1–2 weeks post‐KT and before initiation of DAA. Median (IQR) viral load (VL) in log copies/ml was one log lower in ezetimibe group versus non‐ezetimibe group (4.1 [3.7–5.3] vs. 5.1 [4.4–5.5], P = .01), and highest VL was also lower in ezetimibe group (4.2 [3.7–5.4] vs. 5.4 [4.7–5.9], P = .006). We concluded that ezetimibe bridge therapy might be associated with reduction in HCV VL while waiting for DAA initiation in HCV+ to HCV negative KT recipients.